Perlindungan Hukum Bagi Pasien dan Tanggung Jawab Medis Dalam Praktik Kesehatan - Ika Wahyuni (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2023)
This study aims to: 1) analyze the legal protection provided to patients in health practices, 2) explain the limits of medical responsibility that are the obligations of health workers, and their implications for safe and professional health care practices. This study is a normative legal study using a statutory approach and a conceptual approach. The legal materials consist of primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials are analyzed using legal interpretation, legal theories, and legal principles. The results of the study show that the legal framework for patient protection in Indonesia, which is regulated through Act No. 17 of 2023 concerning Health and Regulation of the Minister of Health No. 11 of 2017 concerning Patient Safety, guarantees patients' rights to safety, information, and professional services, and emphasizes the obligations of medical workers according to professional and ethical standards. The limits of medical responsibility are regulated through Article 57 paragraph (1) of Act No. 17 of 2023, with the application of the principles of caution, justice, and legal certainty as guidelines. These provisions ensure that healthcare practices are safe, professional, and lawful, while minimizing the risk of malpractice and comprehensively protecting patient rights.